Энергетический расчет фильтро-компенсирующего преобразователя с накопительным аккумулятором - Миколаец, Д.А. (Технічна електродинаміка, 2012)
The paper presents a method of calculating the energies, on the basis of their representation in the form of a piecewise continuous function, for the filter-compensating converter (FCC) with storage accumulator. Analysis of the scheme by the condition of balance of power are shown. Derived power relations that allow to calculate the parameters of circuit elements. The structural scheme of device and graphs showing the processes in the FCC are shown.